With All Your Heart - Murray, Donal (Studia canonica, 2014)
The relationship between canon law and the human heart may not be an obvious topic. It is nonetheless a necessary subject of reflection if we are to implement the ecclesiology of Vatican II as the revised Code set out to do. This leads us to reflect on what might have been the aim behind Pope Paul VI’s proposal for a Lex fundamentalis Ecclesiae. More importantly it calls on all members of the Church to see their lives in the light of the commandment of love on which the law and the prophets depend. For canon law as for everything in the Church it poses the challenge of how the Church’s laws and structures can be at the service of the mystery which, as Pope Francis recently remarked to the bishops of Brazil, 'enters through the heart'.